Barley starch, structure and properties - Eriksson, Jenny (2012)
Starch is a naturally occurring substance in most plants and is used as energy storage. It is a component that mainly consists of amylose and amylopectin. Together they build a complex pattern which gives starch its specific properties. The proportion of amylose and amylopectin varies in different plants but generally starch consists of 25 % amylose and 75 % amylopectin. There have been discoveries of barley varieties containing 100 % amylopectin called “waxy starches” or “waxy barley” as well as varieties that have a high content of amylose, around 70 % and these are called “amylotypes”. Amylopectin as well as amylose consists of α-1, 4 linkage between α-ᴅ-glucose. The great difference between them is the degree of branching. In amylopectin, 4 to 5 % of the glycosidic bonds are α-1, -6 bonds. The average chain length is shorter than in amylose, but with more branching it is a larger molecule. With the different branching the molecule forms an intricate structure. The chains of amylopectin are believed to be organized in clusters which bind to each other with the assistance of a certain type of chains. In this study six different barley varieties were investigated according to starch structure and properties. In order to fully characterize these samples, several different methods were used in a combination. Gel Permeation Chromatography was performed to separate the amylose from the amylopectin, and then the collected fractions were analysed with the Phenol-Sulphuric acid method. The properties of the samples were examined with RapidViscoAnalyser that measures the viscosity during a temperature increase and decrease with continuous stirring. The chain length distribution of amylopectin and its φ, β-limit dextrins were studied with High Performance Anion Exchange Chromatography - Pulsed Amperometric Detection. The amylose content varied between 0.6 % and 48 % in the different starches. The RVA demonstrated that the more amylose and fibres the samples contained the higher final viscosity. The High Performance Anion Exchange Chromatography - Pulsed Amperometric Detection showed no clear indication of difference between the samples and to establish the whole structure of these six barley varieties and their properties more research is necessary.